Fracture mechanics as a tool in failure analysis — Prospects and limitations. (September 2015) - Zerbst, U.; Klinger, C.; Clegg, R.
Abstract: Although fatigue crack propagation and fracture cause a large part of failure events in industrial practice, fracture mechanics in failure analysis seems to be still a side issue. Starting from an introduction into important basic questions of failure analysis and fracture mechanics, the authors specify what kind of questions in failure analysis can be effectively solved by fracture mechanics (and which can't). They illustrate their discussion with a number of 13 case studies from the literature. Much more pronounced than in the design stage the benefit of fracture mechanics in failure analysis depends on its accuracy. This is limited by both, intrinsic factors of the method and the availability and quality of the input information. The authors discuss the various aspects and provide the reader with some background information which, as they believe, will be helpful for better understanding the prospects and limitations of fracture mechanics in failure analysis and the conditions of its application. Highlights: Systematic discussion of fracture mechanics application in failure analysis — what is possible, what is of no or minor value Definition of basis questions of fracture mechanics in failure analysis context Specifying requirements for fracture mechanics input information including its accuracy Thirteen case studies for illustration